Clinical and biochemical assessment of a modified evaporated milk for infant feeding. Issue 3 (March 1977) - Belton, N R; Cockburn, F; Forfar, J O; Giles, M M; Kirkwood, J; Smith, J; Thistlethwaite, D; Turner, T L; Wilkinson, E M
Abstract : A clinical and biochemical evaluation has been made of a new milk formula, Modified Carnation milk (MCM), based on cows' milk but with the mineral content and concentration of caloric nutrients altered to make it correspond more closely to human milk. MCM produced higher plasma calcium and magnesium concentrations in 6-day-old infants than those produced by unmodified evaporated and dried milks, achieving concentrations closer to those of breast milk. Plasma free amino acid concentrations in MCM-fed infants are nearer breast-fed values than those in unmodified milk-fed infants where higher individual plasma amino acid concentrations persist during the first 3 months. MCM-fed infants had low plasma urea concentrations and lower urine osmolalities at 6 days, 3 weeks, 6 weeks, 3 months, and 6 months than infants fed on the evaporated and dried milks, and similar plasma urea and urine osmolalities to those of breast-fed infants. MCM is likely to be superior to unmodified evaporated and dried milks in preventing convulsions of the hypocalcaemic/hypomagnesaemic/hyperphosphataemic type, and seems less likely to cause hypertonic dehydration. MCM is easily prepared, readily accepted by babies, and appears to be nutritionally adequate for the feeding of term infants.